2013
DOI: 10.1007/s00228-013-1630-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and main features of adverse drug reactions leading to hospital admission

Abstract: Over 4 % of urgent hospitalizations are caused by ADRs, which are dose-related and predictable in more than 90 % of cases. The main risk factors are advanced age and polypharmacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
106
3
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(128 citation statements)
references
References 41 publications
13
106
3
6
Order By: Relevance
“…People with cognitive impairment are even more vulnerable to ADRs than those without cognitive impairment due to the neurochemical changes in neurotransmitter substances that occur especially in people with dementia [1]. The ADRs may also occur at a higher frequency, and to a higher degree, among this patient group [1, 6], and it is seen that the risk of experiencing ADRs increases among old people (OR 1.59, 95% CI 1.10–2.29) [7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with cognitive impairment are even more vulnerable to ADRs than those without cognitive impairment due to the neurochemical changes in neurotransmitter substances that occur especially in people with dementia [1]. The ADRs may also occur at a higher frequency, and to a higher degree, among this patient group [1, 6], and it is seen that the risk of experiencing ADRs increases among old people (OR 1.59, 95% CI 1.10–2.29) [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Older people with cognitive impairment are particularly vulnerable to drug effects and ADRs, and it is seen that hospital admissions among this patient group are often due to ADRs [3, 7, 20]. It is therefore important to identify and pay attention to PIM use in order to improve the drug use among this vulnerable group of people.…”
Section: Introductionmentioning
confidence: 99%
“…12,16 To date, the majority of studies addressing the problem of polypharmacy have been in the geriatric population where the risk for adverse drug reactions has been shown to be associated with the number of drugs taken. 17,18 Of the few studies that have examined polypharmacy in the SCI population, a recent retrospective study of 175 patients with chronic SCI reported over 300 drugs being administered in more than 19 classes of medications. 19 In addition, a recent study examined the combination use of opoid and anticonvulsant therapy for neuropathic pain in the SCI population.…”
Section: Introductionmentioning
confidence: 99%
“…Pedrós y colaboradores titulado Prevalencia, factores de riesgo y principales características de las reacciones adversas a los medicamentos que conducen a la hospitalización 8 , el cual se realizó durante un periodo de 120 días, encontrándose que la polifarmacia y la edad eran los principales factores de riesgo para desarrollar reacciones adversas, lo cual se incrementaba con el número de medicamentos que usaban al momento de la admisión al hospital: 3-5 drogas con un OR 5.07 (IC 95% 2.71 -9.59), 6-9 drogas OR 5.90 (IC 95% 3.16-11.96), > 10 drogas OR 8.94 (IC 95% 4.73-16.89). Al compararse estos resultados con nuestra investigación, se encuentra resultados similares; en nuestro estudio un probable exceso de riesgo para presentar RAM fue la polifarmacia (> 5 medicamentos) con un OR 3.30 IC 95% 1.96-5.57 cuando se ajustaron varios confusores.…”
Section: Discussionunclassified